Investigating Teachers’ Role in Enhancing Efl Classroom in the Digital Era: Indonesian High School Students’ Voices - Abror, Sujud Nurul; Wahyuningsih, Sri (ELITE Association Indonesia, 2023)
The objective of this study is to explore the role of English teachers in the digital age with a qualitative approach by interviewing six Indonesian high school students. They were selected because they frequently use social media for enhancing their English. Individual interviews were conducted to gain an in-depth understanding of their perspectives. The findings indicate that the accessibility of social media significantly helps students in learning English. However, the teacher maintains to be the primary source of knowledge in EFL classes. In case students do not comprehend the topic being taught, they search for further explanations on social media. Students also use social media to improve their English language skills. Meanwhile, students are more comfortable when learning through social media because they can use search engine tools to look up any topic without feeling embarrassed about asking questions. The conclusion reached by the research is that the role of teachers is limitless in the classroom based on the findings. The study recommends that English teachers integrate social media into EFL classrooms and create an enjoyable environment so that students can participate thoroughly.